Synthesis and In Vitro Antibacterial Activity of Novel Naphthyridinone Derivatives. Issue 21 (6th June 2019) - Sun, Bin; Chen, Jianwei; Ye, Fei; Lu, Yaojia; Xu, Guiqing; Mao, Longfei; Gao, Yuan; Zhang, Huawei; Wang, Hong; Peng, Lizeng
Abstract: Naphthyridinone has been reported exhibiting strong antibacterial activity. Now, this study describes a series of novel hydrochloride salts of 5, 6, 7, 8‐tetrahydro‐1, 6‐naphthyridin‐2‐(1 H )‐one derivatives (10 a –10 l ) as potential antibacterial agents and corresponding synthetic routes. The majority of analogues exhibit antibacterial activity against Gram‐negative bacteria ( E. coli ) and Gram‐positive bacteria ( S. aureus ). Several of them (10 a, 10 b, 10 h and 10 i) showed strongly antibacterial activity towards E. coli . Compound 10 l is also the first reported compound to exhibit quorum sensing inhibitory activity against C. violaceum ATCC 12472. The presence of quorum sensing inhibitory compound indicates its potential use in the treatment of bacterial infections. Abstract : This study describes a series of novel hydrochloride salts of 5, 6, 7, 8‐tetrahydro‐1, 6‐naphthyridin‐2‐(1 H )‐one derivatives (10 a ‐10 l ) as potential antibacterial agents and corresponding synthetic routes. Among them, 10 a, 10 b, 10 h and 10 i showed strongly antibacterial activity towards E. coli . Compound 10 l exhibited quorum sensing inhibitory activity against C. violaceum ATCC 12472 and was performed to explore the possible inhibitory mechanism by molecular docking.